Flexibilizações políticas e rupturas do processo democrático : uma análise dos pareceres do TCE-ES entre os anos de 2010 e 2017 - Gonçalves, Gabriel Garschagen (2019)
The concept of democracy in modern societies is intrinsically linked to the existence of control mechanisms that ensure accounts render transparency of acts and if the rulers could be responsibilized for their actions and omissions. The contemporary term that illustrates this desired duality of control and responsability is accountability, which is repeatedly identified in the literature as indicative of the democratic quality of a country. As the current institutional design assigns to the audit courts the role of assisting the Legislative Branch in the external control of public accounts, distortions in this process will result in poor accountability of government officials and, consequently, weakening democracy. In recent years, situations have been identified, especially in the context of the annual accounts judgments of the governors of the State of Espirito Santo, which raised questions about a possible political activity of the State courts of account, frontally colliding with its eminently technical role assigned by the Constituent Assembly. Thus, this paper intends to analyze the opinions and reports issued that subsidized the preliminary report, sent to the Legislative Branch, seeking to verify if the opinions of the Court and other responsible persons follow strictly what is defined by the current norms, or, alternatively, situations of flexibility to the norms are verified, which provokes to the occurrence of politicization in this institution. The results support the hypothesis of a political performance of the courts of account of the State of Espirito Santo between the years 2010 and 2017 provoked, mainly, by the indication of members with strong political, and even personal, connection with the two governors of the period (Paulo Hartung and Renato Casagrande). It was demonstrated that the political behavior is not restricted to the activities of the counselors, being observed over the years under analysis, with very few exceptions, the same behavior by eminently technical agents, such as prosecutors of the Public Prosecutor's Office (MPC) and auditors of the instructional body of the court and of the internal control of the Executive Branch, indicating the existence of an establishment in these institutions. These facts show that the occurrence of flexibilizations to the norms in force for the benefit of the state governors resulted, during the analyzed period, in the lack of accountability of the political agents and, consequently, in a rupture in the democratic process. Faced with the facts raised, it becomes evident the need for democratization of the courts of account, obligatorily, permeating aspects that strengthen social control.